Methodologies in the identification, analysis, and measurement of visual pollution the case study of intramuros - Barroga, Stanley Don S.; Palarca, Honorio T. (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
The problem of visual pollution in the Philippines has been increasingly evident, and the people are starting to become aware of it. But in order to create effective solutions, a deep understanding of the problem should first be established. This thesis was aimed to identify, analyze, and measure the visual pollution present in Intramuros. To achieve this goal, the application of the Indirect and Direct Method of Landscape Evaluation was executed. These methods led to two things: (1) the identification of components— which are attributes and indicators, that make up a visual landscape; and (2) the understanding of how it is perceived by the observer through a survey and interviews, which is quantified by ratings. To further understand the relationship of indicators and ratings with each other, a series of correlational studies was done. This resulted to the establishment of Disturbance, Stewardship, and Image Rating as the primary descriptors of visual pollution. A weighted average formula was then established, which quantified the visual pollution of Intramuros through indicator values and response ratings. It was concluded that visual pollution, through research-based methodology, can be identified, analyzed, and measured.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Visual landscape -- Intramuros; Visual pollution -- Intramuros; Visual pollution score -- Intramuros